Das Paar als Reproduktionsinstanz? Paare im Fokus von humangenetischer Beratung in Ost- und Westdeutschalnd während der 1950er bis 1980er Jahre - Heinemann, Isabel 1971- (Geschichte und Gesellschaft, 2023)
After 1945, human genetic counseling in both German states focused on the married couple and its reproduction. While West German geneticists demanded “preventive counseling” to protect the national gene pool, their East German counterparts highlighted the “happiness of the individual,” though they did not shy away fromlarge register projects and “negative eugenics.” Clients, especially women, ceased to be passive objects of human geneticists’ interventions and became active subjects, building their marriages and families with the help of expert advice. The article proposes a gendered reading of human genetic counseling in both German states with a particular focus on knowledge circulation and the agency of clients.